Herpes Simplex Virus 1 Induces Brain Inflammation and Multifocal Demyelination in the Cotton Rat Sigmodon hispidus - Boukhvalova, Marina S. (J Virol, 2019)
Demyelinating central nervous system (CNS) disorders like multiple sclerosis (MS) and acute disseminated encephalomyelitis (ADEM) have been difficult to study and treat due to the lack of understanding of their etiology. Numerous cases point to the link between herpes simplex virus (HSV) infection and multifocal CNS demyelination in humans; however, convincing evidence from animal models has been missing. In this work, we found that HSV-1 infection of the cotton rat Sigmodon hispidus via a common route (lip abrasion) can cause multifocal CNS demyelination and inflammation. Remyelination occurred shortly after demyelination in HSV-1-infected cotton rats but could be incomplete, resulting in “scars,” further supporting an association between HSV-1 infection and multifocal demyelinating disorders. Virus was detected sequentially in the lip, trigeminal ganglia, and brain of infected animals. Brain pathology developed primarily on the ipsilateral side of the brain stem, in the cerebellum, and contralateral side of the forebrain/midbrain, suggesting that the changes may ascend along the trigeminal lemniscus pathway. Neurologic defects occasionally detected in infected animals (e.g., defective whisker touch and blink responses and compromised balance) could be representative of the brain stem/cerebellum dysfunction. Immunization of cotton rats with a split HSV-1 vaccine protected animals against viral replication and brain pathology, suggesting that vaccination against HSV-1 may protect against demyelinating disorders. IMPORTANCE Our work demonstrates for the first time a direct association between infection with herpes simplex virus 1, a ubiquitous human pathogen generally associated with facial cold sores, and multifocal brain demyelination in an otherwise normal host, the cotton rat Sigmodon hispidus. For a long time, demyelinating diseases were considered to be autoimmune in nature and were studied by indirect methods, such as immunizing animals with myelin components or feeding them toxic substances that induce demyelination. Treatment against demyelinating diseases has been elusive, partially because of their unknown etiology. This work provides the first experimental evidence for the role of HSV-1 as the etiologic agent of multifocal brain demyelination in a normal host and suggests that vaccination against HSV-1 can help to combat demyelinating disorders.